Deep－Source Ore－Forming Materials and Prospecting of Gold Deposits in Eastern Hebei,China - 王宝德 牛树银 孙爱群 李红阳 (Acta geochimica, 2003)
Eastern Hebei Province is one of the important gold mineralization areas in North China,and detailed investigations have been made in this area.Different mineralization models and different ore-formng surces have been proposed for the gold deposits in this area.As more detailed work was made and more information has been accumulated,it is necessary to make a new investigation on gold metallogenesis and its source.This paper presents the data about 13 gold deposits(occurrences.)It is concluded that the element gold came from the deep mantle.Different models of metallogenesis substantially describe such processes that ore-forming fluids were involved in metallogenesis in different favorable loci.Gold ore prospecting should be focused on fluid channel ways and favorable structures.